Attachment Styles as Predictors of Suicidal Behavior in School Going Adolescents - Mwania, Jonathan; Owino, Walter; Kimatu, Josphert (International Journal of Psychology, 2023)
Purpose: Secondary school students face numerous challenges as they balance academic challenges, parental and peer pressures, emotional issues related to puberty changes and adolescence expectations. They also grapple about not knowing what the future holds in terms of career paths. As a result of these challenges, it is common for adolescents to have suicidal thoughts that may lead to suicide attempts.. Suicide is among the leading cause of death in young people and is prevalent worldwide. Suicidal behavior has been associated with attachment security in studies but few of these studies have been done in Kenyan adolescents. This study filled this gap by investigating whether attachment styles predicted suicidal behavior in students attending secondary schools in Nairobi, Kenya. Methodology: The study was correlational in design and was based on the attachment theory. Three hundred and sixty seven randomly selected students completed self-report measures consisting of the Attachment Styles Questionnaire and a Suicidal Behavior Scale. Findings: Results of multiple regression showed that that attachment styles significantly predicted suicidal behavior (F = 36.125, P < .000) and 30% of variance in suicidal behavior was attributed to the attachment styles (R2 = .300). Preoccupied (Î² = .487, P < .001) and dismissing (Î² = .122, P = .018) attachment styles predicted suicidal behaviors. Unique Contribution to Theory, Practice and Policy: The contribution to knowledge of this paper is that it provides a theoretical and practical contribution on the importance of attachment styles in predicting suicidal behaviours. The results of the study show that attachment security plays an important role in adolescents' suicide behavior as insecurely attached students have a higher risk of suicide.Basically, the study contributed to a theoretical enhancement of the current level of knowledge on the existing literature on attachment styles and suicidal behaviours, achieved by testing empirically the adolescent behaviour. Therefore, suicide prevention programs should take into account adolescents' attachment styles.